Personality of Elementary School Students Based on Five Big Traits Theory and the Correlation with Self-Regulated Learning - Rini, Titis Angga; Cahyanto, Bagus; Nuraini, Ni Luh Sakinah; Cholifah, Puri Selfi (Journal of Educational Sciences, 2025)
This research is based on the finding that student personality also influences the success of learning, especially in self-regulated learning. This study investigates the personality of elementary school students and relates it to self-regulated learning. Understanding students' personalities is a teacher's task and key to academic success, for example, in its relationship to good self-control and organization in learning. Student personality is based on Trait theory, which classifies into openness to experience (x1), conscientiousness (x2), extraversion (x3), agreeableness (x4), and neuroticism (x5). Personality and self-regulated learning were explored through a self-assessment questionnaire consisting of thirty-five questions for elementary school-aged students. The results were analyzed partially and simultaneously to reveal their correlations with each other. The data in the study showed that partially conscientiousness and neuroticism were positively correlated with self-regulated learning, while no correlation was found for other behaviors. However, simultaneously, all (x) were correlated with students' self-regulated learning (y). In self-regulated learning, these results can be a basis for constructing good habits and self-control for students from the beginning of elementary school. The implications of understanding student personality can be a reference in selecting appropriate learning strategies.